PRODUK OLAHAN BAKSO MUJAIR SEBAGAI INOVASI MAKANAN JAJANAN PADA ANAK SEKOLAH DASAR - Grace Kerly Lony Langi; Irza N Ranti; Rudolf Boyke Purba; Fernando M Tumimomor (POLTEKKES KEMENKES MANADO, 2022)
ABSTRACT Children are the nation investment, because they are the nation’s next generation. The optimal growth and development of school-age children depends on the provision of good and correct quality and quantity of nutrition. Insufficient intake of children is caused by lack of energy and protein that is not in accordance with the needs in the long term. This study aims to determine the level of preference for tilapia meatball processed products as healthy snack for children at Toulimembet State Elementary School. This type of research uses an experimental method with an organoleptic test research design in which researchers measure the level of preference for processed products of tilapia meatballs. Approved by the Health Research Ethics Commission of the Health Ministry of Health Manado No. 01/04/110/2021. The results of the level of preference for the color, taste, texture and scent of the tilapia meatball product. 2 times of testing there were many who chose to like the color test with a percentage of 69,8%, in the taste test many chose to like it with a percentage of 62,8% for the texture test. Many chose to like it with a percentage of 53,5% and for the scent test, many chose to like it with a percentage of 65,1%. The conclusion of the panelist school children’s preference for taste was that they chose very much like the processed product of tilapia Meatballs, which was 32,6% and color 69,8%. While the texture of processe products of tilapia meatballs a is preferred by 53,5%, as well as the aroma of processed products of tilapia meatballs, which is 69,8%.